2013
DOI: 10.1002/jmv.23810
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interplay among Th17, Th1, and Treg cells in HIV‐1 subtype “C” infection

Abstract: CD4 T cell depletion is central to HIV pathogenesis and disease progression. Different subsets of CD4 T cells cooperate to combat an infection. Therefore, the immune balance among Th17, Th1, and Treg cells may be critical in HIV immunopathogenesis which is not adequately defined yet. The impact of HIV-1 infection on the interplay of Th17/Th1/Treg cells in HIV-1 infected Indian individuals was examined in the present study and report that HIV-1 Gag specific peripheral blood Th17 cells were significantly deplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
1
8
1
1
Order By: Relevance
“…As this last T-cell subset is known to suppress T-cell responses, negative correlations with levels of immune activation could be expected, however we found direct correlations with CD8 + T-cell activation and VL, and an inverse relationship with CD4 counts. These results are in line with recent studies which described direct correlations between Treg cells and T-cell activation 22 or disease progression 23 , and inverse correlations with CD4 frequencies 22 , thus supporting the hypothesis of a detrimental role for this subset or the expansion of non-functional Tregs during HIV infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As this last T-cell subset is known to suppress T-cell responses, negative correlations with levels of immune activation could be expected, however we found direct correlations with CD8 + T-cell activation and VL, and an inverse relationship with CD4 counts. These results are in line with recent studies which described direct correlations between Treg cells and T-cell activation 22 or disease progression 23 , and inverse correlations with CD4 frequencies 22 , thus supporting the hypothesis of a detrimental role for this subset or the expansion of non-functional Tregs during HIV infection.…”
Section: Discussionsupporting
confidence: 91%
“…Within the PHI cohort, we found a trend towards a Th17 reduction between baseline and one year p.i samples, however significant differences were not reached in line with previous studies 13 23 . However, at baseline we found a clear difference between RPs and TPs in relation to CD8 + T-cell activation, VL and Th17 counts.…”
Section: Discussioncontrasting
confidence: 48%
“…In animals Treg depletion during Mtb infection reduced pathology and bacterial burden, while the reverse was seen following adoptive transfer of Tregs (63,64), suggesting that these cells contribute significantly to the regulation of bacterial containment in vivo. Acquired immunodeficiencies due to HIV or impaired immunity due to T2DM may alter the balance between effector and regulatory T cells (65)(66)(67)(68)(69)(70).…”
Section: Immuneregulation and Th17 Immunity In Tbmentioning
confidence: 99%
“…We observed that Mtb stimulation increased the numbers of lymphocytes with a regulatory phenotype over Th1 CD4 + T cells (lower Th1/FoxP3, Th1/Tregs, Th1/uTregs and Th1/FoxP3 + T-bet+ ratios in patients). Other authors suggested that it would be useful for monitoring progression of infection to focus on the study of the relative balance between Th1/regulatory cells rather than on the analysis of a specific cell subset [55]. We discovered 7-OD and DHEA augmented Th1/uTregs ratio, but only 7-OD could reverse the effect of Mtb in terms of the balance of Th1/FoxP3, Th1/Tregs and Th1/FoxP3 + T-bet+ in HIV-TB individuals.…”
Section: Discussionmentioning
confidence: 99%